Efficacy of the Canalith Repositioning Procedure in Benign Paroxysmal (Medicine Today, 2016)
Benign paroxysmal positional vertigo (BPPV) is paroxysms of vertigo occurring with certain head movements, typically looking up or turning over in bed comprising about 20% of Dizziness cases. This study was carried out to evaluate the Efficacy of canalith repositioning procedure(CRP) in BPPV. A randomized clinical trial including 80 patients with BPPV was performed Medicine & Neurology Outpatient Department, Chittagong Medical College Hospital. The patients were randomly divided into two groups. Group A treated by anti-vertigo drug and CRP, Group B treated by anti-vertigo drug alone. All patients were followed up in hospital at one week after & 4 weeks. The rates of effectiveness of CRP treatment and the control treatment for were 86.8% and 59.4%, respectively. There was a significant difference (27.4%) in the outcomes of the CRP & control groups (P